IMPLEMENTASI QUALITY ASSURANCE DALAM MEMBANGUN BUDAYA LITERASI SISWA DI SD MUHAMMADIYAH 1 BANGKALAN - alhindan, qonita (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study aims to evaluate the effectiveness of Quality Assurance implementation in building student literacy culture at SD Muhammadiyah 1 Bangkalan. By identifying aspects that have been successful or unsuccessful, schools can make more appropriate and effective improvements in future literacy programs because this study aims to determine the literacy culture of students at SD Muhammadiyah 1 Bangkalan. The research method in this research is qualitative research. This research explores the views, experiences and perspectives of individuals and groups in relation to literacy, thus providing in-depth insight into how literacy affects daily life and society at large. The results showed that SD Muhammadiyah 1 Bangkalan has implemented Quality Assurance effectively to improve the quality of education. The Quality Assurance process involves regular evaluation of learning activities, teacher training, and adequate use of learning resources. The results of the evaluation are used to identify areas that need improvement and develop an appropriate improvement plan. In addition, this study also revealed that literacy culture has become an integral part of the learning environment at SD Muhammadiyah 1 Bangkalan. Students are encouraged to read actively and apply literacy skills in a variety of subjects. Teachers also provide strong guidance and support in developing students' literacy skills.